Exploring pathways to invest in Ban pig breeding improvements in Son La Province, Northwest Highlands of Vietnam - Le Thi Thanh Huyen; Unger, Fred (International Livestock Research Institute, 2024)
Ban pigs have traditionally been raised by ethnic groups in upland areas. However, these communities are increasingly facing challenges, including declines in genetically pure Ban pig populations, the prevalence of unknown mixed breeds, breeding degradation, inbreeding, low productivity, and the high prices of Ban pigs compared to exotic breeds.